Two-sex life table analysis and digestive physiology of Sitotroga cerealella (Olivier) (Lepidoptera: Gelechiidae) on different barley cultivars. (January 2018) - Karimi-Pormehr, Mohammad Sadegh; Borzoui, Ehsan; Naseri, Bahram; Dastjerdi, Hooshang Rafiee; Mansouri, Seyed Mozaffar
Abstract: The life table parameters and digestive enzymatic activity of Sitotroga cerealella Olivier (Lepidoptera: Gelechiidae), an important insect pest of grains, were studied under laboratory conditions (25 ± 1 °C, relative humidity of 65 ± 5% and a photoperiod of 16: 8 (L: D) h). Seeds of ten barley cultivars including Bahman, CB-84-10, Fajr30, Makuyi, Nosrat, Yousof, 12A1, 13A1, 18A1 and 19A1 were used as host diet. S. cerealella showed the shortest developmental time and the highest survival and fecundity after feeding on cultivar 19A1 . The longest developmental time and the lowest fecundity were on cultivars Bahman and Fajr30, respectively. The gross and net reproductive rates and intrinsic rate of increase were the highest when S. cerealella was reared on cultivar 19A1 . However, a corresponding decrease in these parameters was observed on cultivar Fajr30. Fourth instar larvae fed on cultivar 19A1 showed higher α-amylase activity than those fed on other barley cultivars. However, S. cerealella larvae exhibited no significant difference in proteolytic activity among barley cultivars. Correlation analyses showed that high correlations existed between the life table parameters and α-amylase activity on one side and particle size index on the other. It is suggested that nutritional quality, especially seed hardness, may be the major factor responsible for the susceptibility of barley cultivars to S. cerealella . Graphical abstract: Highlights: Life table and digestive enzymatic activity of S. cerealella was studied on different barley cultivars. Population growth of S. cerealella was the lowest on Fajr30 (as a resistant cultivar). Seed hardness was the major factor responsible for the susceptibility of barley cultivars to S. cerealella .